City and country the historical evolution of urban-rural systems - Thomas, Alexander R., 1969- (Studies in urban-rural dynamics, 2021)
"City and Country traces the evolution of urban-rural systems 7,000 years ago into the modern global order and argues that at the heart of the logic of capitalism is an even deeper logic: urbanization is based on urban dependency"--